Metabolic adaptations of Leishmania donovani in relation to differentiation, drug resistance, and drug pressure. Issue 2 (11th September 2013) - Berg, Maya; Vanaerschot, Manu; Jankevics, Andris; Cuypers, Bart; Maes, Ilse; Mukherjee, Sandip; Khanal, Basudha; Rijal, Suman; Roy, Syamal; Opperdoes, Fred; Breitling, Rainer; Dujardin, Jean‐Claude
Summary Antimonial (sodium stibogluconate, SSG) resistance and differentiation have been shown to be closely linked in Leishmania donovani, with SSG‐resistant strains showing an increased capacity to generate infectious (metacyclic) forms. This is the first untargeted LC‐MS metabolomics study which integrated both phenomena in one experimental design and provided insights into metabolic differences between three clinical L. donovani strains with a similar genetic background but different SSG‐susceptibilities. We performed this analysis at different stages during promastigote growth and in the absence or presence of drug pressure. When comparing SSG‐resistant and SSG‐sensitive strains, a number of metabolic changes appeared to be constitutively present in all growth stages, pointing towards a clear link with SSG‐resistance, whereas most metabolic changes were only detected in the stationary stage. These changes reflect the close intertwinement between SSG‐resistance and an increased metacyclogenesis in resistant parasites. The metabolic changes suggest that SSG‐resistant parasites have (i) an increased capacity for protection against oxidative stress; (ii) a higher fluidity of the plasma membrane; and (iii) a metabolic survival kit to better endure infection. These changes were even more pronounced in a resistant strain kept under SbIII drug pressure.